SAT0206 Dynamic magnetic resonance imaging of the wrist: a comparison of patients with active rheumatoid arthritis, rheumatoid arthritis in remission, and psoriatic arthritis. (1st June 2001) - Cimmino, MA; Iozzelli, A; Magnaguagno, F; Parodi, M; Gandolfo, C; Maio, T; Silvestri, E; Palazzolo, M; Innocenti, S; Garlaschi, G
Abstract : Background: Objective quantification of synovial membrane inflammation is an important goal of rheumatology research. Recently, magnetic resonance imaging (MRI) has been used to evaluate synovitis in rheumatoid arthritis (RA). 1, 2 Objectives: Our work is concerned with an evaluation of synovitis in patients with active RA, RA in remission, and psoriatic arthritis (PsA) in comparison with normal controls (CO). Methods: 16 patients with RA according to the 1987 ACR criteria, of whom 5 were in complete clinical remission, 6 patients with PsA, and 2 CO were studied. MRI was performed with a 0.2T dedicated device (Artoscan, Esaote, Genova, Italy). The sequence used was a Spin Echo (TR/TE = 100/16 ms, matrix = 160 × 128, FOV = 50 × 150, slice thickness = 5 mm). A bolus of 0.2 ml/kg of gadopentetate dimeglumine was injected intravenously and fast images of three slices of the wrist were repeated every 20? thereafter. The enhancement ratio was calculated both as rate of early enhancement (REE) and as relative enhancement (RE). The signals from a small circular ROI in the region of maximal enhancement and from a larger segmented region including most of the enhanced synovial membrane were evaluated. The signal was normalised to the bone to reduced noise. Results: Both REE and RE were significantly higher in active RA vs. inactive RA (p = 0.003), PsA (p = 0.002), and CO (p = 0.0002). In addition, RE and REE were higher in inactive RA than in CO (p = 0.008). Results from the analyses using the small ROI and the segmented ROI showed a good correlation (mean R = 0.75). REE resulted slightly more sensitive than RE. Conclusion: Dynamic MRI is a useful method to evaluate synovitis by allowing quantitative estimation of the synovial enhancement. This promising technique is able to differentiate active from inactive RA, as well as RA from PsA and CO. The evaluation of a small area of the synovial membrane seems to be equally effective than the more time-consuming segmentation. References: Cimmino MA, et al . Semin Arthritis Rheum. 2000;30:180–95 Klarlund M, et al . Scand J Rheumatol. 2000;29:108–15